2015
DOI: 10.1016/j.molimm.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the ERAD ubiquitin E3 ligases for viral and cellular targeting of MHC class I

Abstract: HighlightsE3 ubiquitin ligases play a central role in viral and cellular degradation of MHC-I.HCMV US2 and US11 hijack the mammalian ERAD machinery to induce MHC-I degradation.We identified the TRC8 and TMEM129 E3 ligases as crucial for US2/11 function.The US2/11 degradation hubs are flexible and enable viral evasion of different immune functions.Cellular quality control of MHC-I is controlled by the HRD1/SEL1L E3 ligase complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…For select quantity control substrates, bona fide substrate-specific adaptors have been identified that bridge the substrate and ERAD machinery, functioning as substrate identification and recruitment factors. For example, the viral US2 and US11 proteins deliver major histocompatibility complex class I proteins to, respectively, the E3 ligase Trc8 (translocation in renal carcinoma on chromosome 8 protein) (167, 186) and TMEM129 (184, 186, 187). Other examples include the sterol-regulated recruitment of HMGCRtotheE3 ligase gp78 by Insig (insulin-induced gene protein) 1 and 2 (24, 155, 166) and the activation-dependent recruitment of inositol triphosphate receptors to the E3 ligase RNF170 by Erlin (endoplasmic reticulum lipid raft–associated protein) 1 and 2 (101, 135, 195).…”
Section: Erad Mechanismmentioning
confidence: 99%
“…For select quantity control substrates, bona fide substrate-specific adaptors have been identified that bridge the substrate and ERAD machinery, functioning as substrate identification and recruitment factors. For example, the viral US2 and US11 proteins deliver major histocompatibility complex class I proteins to, respectively, the E3 ligase Trc8 (translocation in renal carcinoma on chromosome 8 protein) (167, 186) and TMEM129 (184, 186, 187). Other examples include the sterol-regulated recruitment of HMGCRtotheE3 ligase gp78 by Insig (insulin-induced gene protein) 1 and 2 (24, 155, 166) and the activation-dependent recruitment of inositol triphosphate receptors to the E3 ligase RNF170 by Erlin (endoplasmic reticulum lipid raft–associated protein) 1 and 2 (101, 135, 195).…”
Section: Erad Mechanismmentioning
confidence: 99%
“…Furthermore, SEL1L variants have been identified in human patients with autoimmune thyroid diseases (Ban et al, ), Alzheimer's (Saltini et al, ), Sjögren's syndrome (Barrera et al, ) and in cardiovascular pathogenesis (Kraus et al, ). Viral degradation of MHC‐I chain also relies on the HRD1/SEL1L complex (van den Boomen & Lehner, ). In Finnish Hound dogs, mSEL‐1L was proposed to be a candidate gene responsible for early‐onset progressive cerebellar ataxia (Kyostila et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…US11 requires the ERAD machinery defined by the E2-recruitment protein AUP1, UBXD8 (ubiquitin regulatory X domain 8) [ 18 ], the E3 ligase TMEM129 [ 19 , 20 ], the E2 ubiquitin-conjugating enzyme Ube2J2 [ 19 , 20 ], and the polytopic membrane protein Derlin1 [ 21 , 22 ]. Although the ERAD adapter SEL1L [ 23 ] had previously been linked to US11 function, later work suggested that SEL1L may instead be involved in the degradation of US11 itself [ 24 ], US2 operates with a different set of cellular factors. The E3 ligase RNF139 (TRC8) [ 25 ] is required for US2 function and the thiol oxidoreductase PDI is thought to aid in the release of MHC I heavy chains from US2 prior to their degradation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%